Hubungan Interpersonal Communication Skills dengan Kualitas Pertemanan Remaja Diorganisasi Pencak Silat: Penelitian - Malik Maulana Ibrohim; Rusmiyati; Anis Tri Yuliana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine whether there is a relationship between interpersonal communication skills and the quality of friendship among teenagers in the pencak silat organization. This study uses a quantitative approach, the method used is the Pearson product moment correlation method. Data collection techniques in the study are scales/questionnaires and observations. Data analysis techniques in this study use descriptive analysis and inferential statistical analysis with Pearson product moment correlation for hypothesis testing. The results of the study show that there are 50 teenagers who are members of the PSHT pencak silat organization used as research samples, the details of the research sample are 25 green belt students, 10 pink belt students, and 15 plain belt students with a total of 23 female students and 27 male students. Based on the data analysis technique carried out, a correlation value of r = 0.938 was obtained with a significance level of 0.000 which means 0.000 <0.05 then Ha is accepted and Ho is rejected. Ha is accepted meaning there is a relationship between interpersonal communication skills and the quality of friendship among teenagers in the pencak silat organization.